VIOLETA: A descriptive study on victims of sexual violence treated in a Peruvian hospital - Sánchez Horna, Gabrielita del Pilar (2024)
Objective: To identify the characteristics of the victims, features related to the violentevent and the care provided by the VIOLETA (comprehensive care for women andmembers of the family group affected by sexual violence) center, from Januaryto December 2022. Methods: The sample includes the total number of peopleattended (n=40). Information was collected from medical records and the VIOLETAteam database. Socio-demographic information and information related to sexualviolence and its care was collected. Results: All patients (n=40) attended were female,mostly adolescent students from Callao, Peru. Sexual violence occurred mainly in thehome and was perpetrated by a person known to them. Only 37% of the victims hadmade a complaint. 17.5% of the victims came within 72 hours of the violence andwere able to receive a complete kit for the prevention of unwanted pregnancies andsexually transmitted infections, including HIV. Forty-five percent of the cases (n=18)were associated with pregnancy, 11 of which were in children under 14 years of age.Conclusion: Adequate knowledge of victims, violent events and care provided during2022 will help us to improve care for victims of sexual violence.